2017
DOI: 10.3390/genes8100254
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of miRNAs and Their Potential Roles in Arsenite-Induced Transformation of Human Bronchial Epithelial Cells

Abstract: The alterations of micro RNAs (miRNAs) and their potential roles in arsenite-induced tumorigenesis are still poorly understood. In this study, miRNA Array was used to detect the expression level of miRNAs in human bronchial epithelial (HBE) cells that were transformed by 2.5 μM arsenite for 13 weeks. These cells exhibited a neoplastic phenotype manifested by increased levels of cellular proliferation and migration and clone formation. Subsequently, 191 dysregulated miRNAs were identified to be associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Therefore, miR-106b, miR-15b, miR-192b, miR-33b, miR-200b, and miR-141 were involved in the malignant transformation of arsenicinduced lung cancer. 132 The role of HIF-2α regulation of miR-191 was investigated to reveal the mechanisms of angiogenesis and metastasis of arsenic-induced lung cancer. 133 In HBE and HUVECs, HIF-2α up-regulated miR-191 via binding to the hypoxia response element (HRE) on the region of miR-191 promoter.…”
Section: Dysregulation Of Mirnas In Arsenic-induced Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, miR-106b, miR-15b, miR-192b, miR-33b, miR-200b, and miR-141 were involved in the malignant transformation of arsenicinduced lung cancer. 132 The role of HIF-2α regulation of miR-191 was investigated to reveal the mechanisms of angiogenesis and metastasis of arsenic-induced lung cancer. 133 In HBE and HUVECs, HIF-2α up-regulated miR-191 via binding to the hypoxia response element (HRE) on the region of miR-191 promoter.…”
Section: Dysregulation Of Mirnas In Arsenic-induced Cancermentioning
confidence: 99%
“…The target genes were enriched in multiple cancer pathways, such as cell cycle, Wnt, and p53 signaling pathways. Therefore, miR-106b, miR-15b, miR-192b, miR-33b, miR-200b, and miR-141 were involved in the malignant transformation of arsenic-induced lung cancer . The role of HIF-2α regulation of miR-191 was investigated to reveal the mechanisms of angiogenesis and metastasis of arsenic-induced lung cancer .…”
Section: Dysregulation Of Mirnas In Arsenic-induced Cancermentioning
confidence: 99%
“…Recent studies have identified new miRNA targets in arsenic carcinogenesis. A miRNA microarray study using arsenite-transformed cells found that miR-33b was downregulated [ 63 ]. miR-33b is a tumor-suppressing miRNA and has been shown to bind to the 3′-UTR of ZEB1, inhibiting its expression, and suppressing Wnt/β-catenin signaling [ 64 ].…”
Section: Arsenicmentioning
confidence: 99%
“…As a novel approach with a large advantage in biomedical research, more and more toxicological studies have employed bioinformatic analysis as a novel method exploring the toxicology, especially in the terms of the toxicological mechanism. The authors have successfully used bioinformatic analysis in the exploration of mechanism toxicology of PhIP and other carcinogens [ 12 , 13 ], and found interesting changes in colonic transcriptome induced by PhIP [ 12 ], suggesting that bioinformatic analysis might be a good utility for exploring the toxicological mechanism of food contaminants. In the last ten years, more and more novel methods of bioinformatic analysis, such as weighted gene correlation network analysis (WGCNA) and linear models for microarray and RNA-seq data (LIMMA) analysis, have been established to identify the potential signaling pathways and plausible central modulating genes (hub genes) [ 14 ] in biomedical research.…”
Section: Introductionmentioning
confidence: 99%